O Uso do Siconv na gestão de convênios públicos: uma análise comparativa entre a Finep e outros órgãos da administração pública federal - Andrade, Miguel Brito de (2014)
This present study aimed at comparing the management of partnership portfolio at the administrative structures which have adopted the Financial Funding Contracts and Partnerships Management System (Siconv) to the Studies and Projects Financing Agency (Finep), which has not adopted it. The focus was to study the impacts on the analysis of processes of providing partial and final accounts, especially the time spent. Partnerships of the seven Ministries which have used the Siconv from 2000 to 2014 were analysed here, which amounts to 82.6% of the funds and 73.7% of the partnerships of that period, representing a sample of 19.428 records. The results revealed that the organizations which adopted the Siconv as it was implementing its features reduced the time spent in the conclusive analysis of an accountability process (rejected or approved) from 84 months in the oldest partnerships to 14 months in the most recent ones whose analysis is all conducted through the Siconv. At the meantime, Finep has kept an average term of 76 months for not benefiting from the advantages of the Siconv, specially from the reduction of the time spent in the analysis of the final accountability processes. This study also reveals that the adoption of the Siconv was profitable to mitigate the amount of partnerships not successfully concluded, what is another negative characteristic in the Finep partnership management process.